Following green chemistry principles for the valorization of lignocellulose waste. On the extraction and characterization of lignin from maritime pine sawdust with novel deep eutectic solvents - Fernandes, Catarina Santos (2020)
Dissertação de Mestrado em Química apresentada à Faculdade de Ciências e Tecnologia